Lineage tracing for multiple lung cancer by spatiotemporal heterogeneity using a multi-omics analysis method integrating genomic, transcriptomic, and immune-related features - Song, Yijun; Zhou, Jiebai; Zhao, Xiaotian; Zhang, Yong; Xu, Xiaobo; Zhang, Donghui; Pang, Jiaohui; Bao, Hairong; Ji, Yuan; Zhan, Mengna; Wang, Yulin; Ou, Qiuxiang; et al. (Frontiers in Oncology, 2023)
Introduction: Distinction between multiple primary lung cancer (MPLC) and intrapulmonary metastasis (IPM) holds clinical significance in staging, therapeutic intervention, and prognosis assessment for multiple lung cancer. Lineage tracing by clinicopathologic features alone remains a clinical challenge, and thus we aimed to develop a multi-omics analysis method delineating spatiotemporal heterogeneity based on tumor genomic profiling. Methods: Between 2012 and 2022, eleven specimens were collected from two patients diagnosed with multiple lung cancers (LU1 and LU2) with synchronous/metachronous tumors. A novel multi-omics analysis method based on whole-exome sequencing, transcriptome sequencing (RNA-Seq), and tumor neoantigen prediction was developed to define the lineage. Traditional clinicopathologic reviews and an imaging-based algorithm were performed to verify the results. Results: Seven tissue biopsies were collected from LU1. The multi-omics analysis method demonstrated that three synchronous tumors observed in 2018 (LU1B/C/D) had strong molecular heterogeneity, various RNA expression and immune microenvironment characteristics, and unique neoantigens. These results suggested that LU1B/C/D were MPLC, consistent with traditional lineage tracing approaches. The high mutational landscape similarity score (75.1%), similar RNA expression features, and considerable shared neoantigens (n=241) revealed the IPM relationship between LU1F/G that were detected simultaneously in 2021. Although the multi-omics analysis method aligned with the imaging-based algorithm, pathology and clinicopathological approaches suggested MPLC owing to different histological types of LU1F/G. Moreover, controversial lineage or misclassification of LU2’s synchronous/metachronous samples (LU2B/D, LU2C/E) traced by traditional approaches might be corrected by the multi-omics analysis method. Spatiotemporal heterogeneity profiled by the multi-omics analysis method suggested that LU2D possibly had the same lineage as LU2B (similarity score: 12.9%, shared neoantigens: n=71); gefitinib treatment, and EGFR, TP53 and RB1 mutations suggested the possibility that LU2E might result from histology transformation of LU2C despite the lack of LU2C biopsy and its histology. By contrast, histological interpretation was indeterminate for LU2D, and LU2E was defined as primary or progression lesion of LU2C by histological, clinicopathological or imaging-based approaches. Conclusion: This novel multi-omics analysis method improves the accuracy of lineage tracing by tracking spatiotemporal heterogeneity of serial samples. Further validation is required for its clinical application in accurate diagnosis, disease management, and improving prognosis.